Educational planning in small states: The case of the Caribbean - Atchoarena, David (UNESCO)
This paper describes a study which attempted to: 1) use the monograph approach to improve knowledge about the situation of education in small countries, particularly in the Caribbean, and 2) distill ideas and techniques to make a technical contribution to educational planning in small countries. Part 1 presents a preliminary reminder of the theoretical and methodological bases of the socio-economic analysis of small countries to explain underlying problems. Part 2 is an in-depth, comparative investigation of small countries' educational problems. The study focuses on two subgroups of islands: those of the eastern Caribbean and those of the French West Indies. Part 3 presents alternatives and options open to educational planners, bearing in mind the constraints imposed by the countries' small size. The report accents long-range forward analysis
Keywords: Small states